Fundamentals of Entrepreneurship (ENT300) : Prisma interior design / : Mohd Hanafiee Jaffar … [et al.] - Jaffar, Mohd Hanafiee; Bahrin, Syazana; Sulaiman, Nur Atikah; Rofie, Syafiqah (2012)
Prisma Interior Design Company is produces the product home interior design such as curtain and wallpaper included accompanied by the kind of style that is modern, classic and traditional Lot 2362, Desa Ilmu, Jalan Datuk Mohammad Musa, 94300, Kota Samarahan, Sarawak that allows the entire family to have originally self-design and not duplicate from the other product home interior design. Prisma Interior Design Company serves family at house. We company also providing in our company too satisfied the customer wants and customer also canto choosing the design in our catalogue.